The Effect of Nurses' Holistic Competence in Chronic Disease Management on Their Attitudes Toward Caregiver Roles - Kerkez, Mujde; Ozturk, Mehmet Hayrullah (Sage Publications Inc, 2025)
The purpose of this study was to investigate the impact of nurses' holistic nursing competence in chronic disease management on their attitudes toward caregiving roles. The sample of the study, which was carried out in descriptive design, consists of 114 nurses (52.6% female and 47.4% male). The research data were gathered with sociodemographic characteristics form, the Holistic Nursing Competence Scale (HNCS), and the Attitude Scale for Nurses in Caregiving Roles (ASNCR). The influence of HNCS, gender, years of job, working style, professional status, weekly working time, and difficulty caring for chronic patients on ASNCR explained 38.1% of the variance. The impact of the ASNCR, gender, years of work in the job, working type, weekly working hours, and having difficulties caring for chronic patients on HNCS explained 54.5% of the variance. Our findings demonstrated the impact of holistic competence on nurses' positive attitudes toward the role of caregiver.
Keywords: caregiver role; chronic diseases; holistic competencies; holistic care; nursing